The effects of sirna-targeting IL-17a receptor in regulating the osteogenic differentiation in stem cells from human exfoliated deciduous teeth - Aduni, Wan Khairunnisaa Wan Nor (2024)
Interleukin-17-A holds significant roles in osteogenic differentiation and bone remodelling mechanism. To date, limited studies describe the effects of small interfering RNA (siRNA) on the expression of IL-17A receptor (IL-17RA) and how the modulation influences the process of osteogenic differentiation. Thus, the present study was to evaluate the effects of siRNA-targeting-IL-17RA on the osteogenic differentiation and the expression levels of osteogenic markers in stem cells from human exfoliated deciduous teeth (SHED). SHED were cultured in complete Minimum Essential Medium α supplemented with osteogenic medium which consists of 50 µg/mL L-ascorbic acid, 10 mM β-glycerophosphate, and 100 nM dexamethasone to induce osteogenic differentiation in SHED for 7 and 14 days. Differentiated SHED were cultured into two conditions: Group 1was treated with optimized concentration of IL- 17A (50 ng/mL) and Group 2 was treated with IL-17A and transfected with optimized concentration of siRNA-targeting-IL-17RA (50 nM) for 48 hours. Mineralisation activity by Alizarin red staining was performed on day 14 and day 21. The effects of siRNA were evaluated by measuring the expression levels of osteogenic markers such as ALP, OPG, RANKL, COL1A1, and RUNX2 by qPCR after 7 and 14 days. Untreated SHED were characterised by positively stained for stem cell markers such as CD90, CD73, and CD105 and were negatively stained for hematopoietic cell marker CD14. Differentiated-SHED showed significant expressions of ALP, COL1A1, and RUNX2 on day 7 and day 14 of differentiation. Staining of IL-17A-treated-SHED by Alizarin red demonstrated an increased calcium deposition compared to untreated SHED. Similarly, the expressions of ALP, OPG, COL1A1, and RUNX2 were significantly upregulated in IL-17A-treated SHED. However, RANKL expression was downregulated. Interestingly, siRNA- transfected SHED showed significant downregulation of ALP, OPG, COL1A1, and RUNX2 while RANKL was upregulated. These findings demonstrate that IL-17A enhances osteogenesis by promoting osteogenic differentiation and that siRNA- targeting-IL-17RA had interfered with the functions of IL-17A/IL-17RA, thus suggesting the importance of IL-17A in mediating the physiological mechanism of bone metabolism.